Privacy Preserving Record Matching Using Automated Semi-trusted Broker - Lazrig, Ibrahim; Moataz, Tarik; Ray, Indrajit; Ray, Indrakshi; Ong, Toan; Kahn, Michael; Cuppens, Frédéric; Cuppens, Nora (Data and Applications Security and Privacy XXIX, 2015)
In this paper, we present a novel scheme that allows multiple data publishers that continuously generate new data and periodically update existing data, to share sensitive individual records with multiple data subscribers while protecting the privacy of their clients. An example of such sharing is that of health care providers sharing patients’ records with clinical researchers. Traditionally, such sharing is performed by sanitizing personally identifying information from individual records. However, removing identifying information prevents any updates to the source information to be easily propagated to the sanitized records, or sanitized records belonging to the same client to be linked together. We solve this problem by utilizing the services of a third party, which is of very limited capabilities in terms of its abilities to keep a secret, secret, and by encrypting the identification part used to link individual records with different keys. The scheme is based on strong security primitives that do not require shared encryption keys.